2022
DOI: 10.1097/rli.0000000000000868
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Computed Tomography Angiography-Based Calcium Scoring

Abstract: PurposeThe aim of this study was to evaluate coronary computed tomography angiography (CCTA)-based in vitro and in vivo coronary artery calcium scoring (CACS) using a novel virtual noniodine reconstruction (PureCalcium) on a clinical first-generation photon-counting detector–computed tomography system compared with virtual noncontrast (VNC) reconstructions and true noncontrast (TNC) acquisitions.Materials and MethodsAlthough CACS and CCTA are well-established techniques for the assessment of coronary artery di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 41 publications
3
49
1
Order By: Relevance
“…Despite the application of iterative reconstructions, this study demonstrated strong correlation and excellent agreement of CACS VNI with CACS TNC at every radiation dose level from 100 to 25%. This is in line with a previous study that evaluated the performance of the same VNI algorithm at standard radiation dose and demonstrated high accuracy for CACS [17]. CACS VNI differed significantly from CACS TNC at standard radiation dose only at 55 keV/QIR1 and dose level 50% but showed no significant differences at any radiation dose level for VNI reconstructions at 60 keV/QIR4.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Despite the application of iterative reconstructions, this study demonstrated strong correlation and excellent agreement of CACS VNI with CACS TNC at every radiation dose level from 100 to 25%. This is in line with a previous study that evaluated the performance of the same VNI algorithm at standard radiation dose and demonstrated high accuracy for CACS [17]. CACS VNI differed significantly from CACS TNC at standard radiation dose only at 55 keV/QIR1 and dose level 50% but showed no significant differences at any radiation dose level for VNI reconstructions at 60 keV/QIR4.…”
Section: Discussionsupporting
confidence: 91%
“…For this study, a commercially available anthropomorphic chest phantom (QRM GmbH, Moehrendorf, Germany) was used with an insert designed for calcium scoring at the heart position. This insert contained nine cylinders with different diameters (1, 3, and 5 mm) and different densities (200, 400, and 800 mg/cm 3 calcium hydroxyapatite), and two calibration rods (one water-equivalent and one with 200 mg/cm 3 calcium hydroxyapatite) as recently described [17]. To simulate the different chest diameters, the phantom was scanned with and without extension rings, resulting in a total of three chest diameters: 300 × 200 mm (small; no extension ring), 350 × 250 mm (medium; extension ring M), and 400 × 300 mm (large; extension ring L).…”
Section: Phantom Setupmentioning
confidence: 99%
See 3 more Smart Citations